Focused ion beam surface treatments of single crystal zinc oxide for device fabrication. (15th December 2016) - Pea, M.; Mussi, V.; Barucca, G.; Giovine, E.; Rinaldi, A.; Araneo, R.; Notargiacomo, A.
Abstract: We investigated 30 kV Ga + ions treatments on (0001) single crystal ZnO in order to assess the potentiality of ion beam based device fabrication on such material. A multi-technique approach combining atomic force microscopy, Raman and energy dispersive X-Ray spectroscopies, and transmission electron microscopy was used to study morphological and structural properties of ZnO upon varying the ion dose. At low doses a shallow defective layer develops showing an increasing defect density as the dose is increased. At higher dose a thinner defective layer with an amorphous layer on top is produced. The ion beam damaged layer on high resistivity ZnO shows enhanced conductivity. KOH based etching removed selectively the damaged ZnO and was found to dissolve rapidly the Ga-rich amorphous layer. The defective layer has an etch rate which depends on the ion dose, and even for prolonged etching processes it was not completely removed. However, conductivity measurements on ion beam fabricated pillars showed that the residual defects do not give a detectable electrical response. These findings indicate that electronic devices and micro-structures with pristine electrical properties of the ZnO crystal can be reliably fabricated by focused ion beam, provided the damaged surface layer is removed by proper etching procedures. Graphical abstract: Highlights: Single crystal (0001) ZnO substrates treated with 30 kV Ga + ions are investigated. The presence of defective and amorphous layers is found depending on ion dose. The ion beam induced damage layer shows enhanced conductivity respect to bare ZnO. KOH based wet etching is found to remove selectively most of the damaged ZnO layer.